2011
DOI: 10.1186/1471-2105-12-186
|View full text |Cite
|
Sign up to set email alerts
|

Extension of the bayesian alphabet for genomic selection

Abstract: BackgroundTwo Bayesian methods, BayesCπ and BayesDπ, were developed for genomic prediction to address the drawback of BayesA and BayesB regarding the impact of prior hyperparameters and treat the prior probability π that a SNP has zero effect as unknown. The methods were compared in terms of inference of the number of QTL and accuracy of genomic estimated breeding values (GEBVs), using simulated scenarios and real data from North American Holstein bulls.ResultsEstimates of π from BayesCπ, in contrast to BayesD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
1,126
0
16

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,032 publications
(1,190 citation statements)
references
References 22 publications
(37 reference statements)
16
1,126
0
16
Order By: Relevance
“…Heslot et al (2012) compared the predictive performance of different linear and non-linear GS models for several traits in plants and found that, overall, linear and non-linear models performed similarly. RKHS seemingly gave the best predictive ability: for example, in 16 out of their 18 comparisons RKHS outperformed Bayes Cp (Habier et al, 2011). The two neural network models gave mixed results.…”
Section: Resultsmentioning
confidence: 99%
“…Heslot et al (2012) compared the predictive performance of different linear and non-linear GS models for several traits in plants and found that, overall, linear and non-linear models performed similarly. RKHS seemingly gave the best predictive ability: for example, in 16 out of their 18 comparisons RKHS outperformed Bayes Cp (Habier et al, 2011). The two neural network models gave mixed results.…”
Section: Resultsmentioning
confidence: 99%
“…Comparisons involved BayesB procedure as implemented in the GenSel package (Habier et al, 2010). These procedures used the model :…”
Section: (V) Computationsmentioning
confidence: 99%
“…As proposed by Habier et al (2011), the priors of all SNP effects were assumed to have a common variance and the effect of an SNP fitted with probability (1 − π) followed a mixture of multivariate Student's t-distributions. Following the estimation of the posterior mean of π from the Bayes Cπ algorithm, the Bayes B algorithm was then invoked using the posterior mean of π.…”
Section: Genotypic Datamentioning
confidence: 99%